Superfine mineral admixture and its application in preparing steam-cured pipe pile concrete

CN123003179APending Publication Date: 2026-10-30SHANGHAI BAOSTEEL NEWBUILDING MATERIALS TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611349223.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-02
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

目前将超细矿粉与石膏激发剂复配用于免蒸压管桩混凝土的工艺方案较少,尚未见针对其配比优化的公开技术指导

Benefits of technology

[0021](1)本发明提供的超细矿物掺合料,以超细矿粉为主要组分,配以适量石膏激发剂,石膏中的SO42-能够与超细矿粉中的活性Al2O3和SiO2反应生成钙矾石(AFt)和水化硅酸钙(C-S-H)凝胶,对超细矿粉的早期水化具有显著的硫酸盐激发作用,用于免蒸压管桩混凝土中可有效提高早期强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a superfine mineral admixture and application of the superfine mineral admixture in preparation of autoclaved-free pipe pile concrete, and the superfine mineral admixture is composed of superfine mineral powder and gypsum activator, and the mass ratio of the superfine mineral powder to the gypsum activator is (80-95):(5-20). 2‑ The superfine mineral powder is used as the main component, the gypsum activator is added in proper amount, the SO4 2‑ The sulphate activator of the superfine mineral powder can significantly accelerate early hydration of the superfine mineral powder and effectively improve early strength of the autoclaved-free pipe pile concrete. Compared with the conventional S95 mineral powder, the admixture can reduce the cement consumption under the condition that the cement is replaced by 50%-60%, and the 1d compressive strength of the concrete can be increased by 15%-30%, so that the pipe pile can meet the strength requirement under the condition of normal-pressure steam curing, the high-pressure steam curing process is omitted, a large amount of industrial by-product gypsum can be absorbed, and remarkable economic benefits and environmental protection benefits are obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of concrete admixture technology, specifically relating to an ultrafine mineral admixture and its application in the preparation of non-autoclaved high-strength pipe pile concrete. Background Technology

[0002] Prestressed high-strength concrete pipe piles (PHC pipe piles) are widely used in foundation engineering for buildings, bridges, and other projects. Traditional PHC pipe piles are cured using high-temperature and high-pressure autoclaving, which consumes a lot of energy and has high carbon emissions. Under the national "dual carbon" target, autoclaved pipe pile technology has become an important direction for the industry's green transformation.

[0003] The core technical challenge of autoclaved aerated concrete (AAC) pipe piles lies in the fact that, after eliminating the high-pressure steam curing process, relying solely on atmospheric pressure steam curing (typically 60-90℃), the concrete needs to reach a strength of C70 or higher within 1-3 days. This places extremely high demands on the early hydration activity of the cementitious materials. Currently, the mineral admixtures commonly used in pipe pile production are mainly S95 grade mineral powder. While these conventional admixtures can improve the later durability and workability of concrete, their pozzolanic reaction rate is slow, and their early activity is low. Under atmospheric pressure steam curing conditions, their contribution to the early strength of concrete is limited, making it difficult to meet the rapid demolding strength requirements of AAC pipe piles. Therefore, developing mineral admixtures with high early activity is the key to a breakthrough in AAC pipe pile technology.

[0004] Ultrafine mineral powder (specific surface area ≥ 600m²) 2 The activity of volcanic ash (per kg) is significantly higher than that of conventional mineral powder, with a clear advantage in early strength. However, when ultrafine mineral powder is used alone, early hydration is still limited by the structural stability of the slag glass, and the improvement in 1-day and 3-day early strength is insufficient to fully meet the requirements for autoclaving-free treatment. On the other hand, the annual emissions of industrial by-product gypsum are huge, and the comprehensive utilization rate needs to be improved. Studies have shown that SO4 leached from gypsum... 2- It can react with active Al2O3 and CaO in mineral powder to form ettringite (AFt), which accelerates the deagglomeration and hydration of slag glass and significantly improves early strength. Currently, there are few process schemes for compounding ultrafine mineral powder with gypsum activator for autoclaved aerated concrete, and there is no publicly available technical guidance on optimizing its mix proportion.

[0005] Therefore, this invention provides an ultrafine mineral admixture for autoclaved concrete pipe piles, with ultrafine mineral powder as the main component and gypsum activator. By optimizing the ratio of the two, the sulfate activating effect of gypsum on ultrafine mineral powder is fully utilized. Compared with S95 mineral powder, this admixture can significantly improve the early strength of concrete, enabling the pipe piles to meet the strength requirements under normal pressure steam curing conditions. This eliminates the need for high-pressure steam curing, reduces production energy consumption and carbon emissions, and also reduces cement usage, resulting in considerable economic and environmental benefits. Summary of the Invention

[0006] In view of the deficiencies in the existing technology, the purpose of this invention is to provide an ultrafine mineral admixture for non-autoclaved concrete pipe piles. The admixture is mainly composed of ultrafine mineral powder and combined with gypsum activator, which can effectively activate the early hydration activity of ultrafine mineral powder. Compared with conventional S95 mineral powder, it can reduce the amount of cement and improve the early strength, so that the pipe pile can reach the strength requirements under normal pressure steam curing conditions.

[0007] To achieve the above objectives, the present invention adopts the following technical solution:

[0008] In a first aspect, the present invention provides an ultrafine mineral admixture for autoclaved concrete pipe piles, comprising ultrafine mineral powder and gypsum activator, wherein the mass ratio of ultrafine mineral powder to gypsum activator is (80-95):(5-20). Within this mass ratio range, the SO4 dissolved by the gypsum activator is... 2- It can fully activate the early hydration activity of ultrafine mineral powder, while avoiding the later volume stability problem caused by excessive gypsum. More preferably, the ultrafine mineral powder and gypsum activator are in a mass ratio of (90~95):(5~10).

[0009] Preferably, the ultrafine mineral powder is ultrafine slag powder obtained by ultrafine grinding of granulated blast furnace slag.

[0010] Preferably, the specific surface area of ​​the ultrafine mineral powder is ≥600m². 2 / kg, density 2.8~3.0g / cm³ 3 Flowability ratio ≥100%, 7d activity index ≥104%, 28d activity index ≥115%, chloride ion content ≤0.06%, loss on ignition ≤1.0%, sulfur trioxide content ≤0.5%.

[0011] Preferably, the gypsum activator is at least one of desulfurized gypsum, phosphogypsum, or fluorogypsum.

[0012] Preferably, the content of calcium sulfate dihydrate or anhydrous calcium sulfate in the gypsum activator is ≥80%.

[0013] Preferably, the specific surface area of ​​the gypsum activator is 300~600m². 2 / kg, to ensure its dissolution rate and activation effect in the gelation system.

[0014] Preferably, the preparation method of the ultrafine mineral admixture is as follows: ultrafine mineral powder and gypsum activator are added to a mixing device according to the ratio, and stirred and mixed for 15-30 minutes until uniform, thus obtaining the finished product; the mixing method is mechanical stirring.

[0015] Secondly, the present invention provides the application of the above-mentioned ultrafine mineral admixture in the preparation of non-autoclaved pipe pile concrete. The application method is to incorporate the ultrafine mineral admixture into the non-autoclaved pipe pile concrete in a manner that partially replaces cement.

[0016] Preferably, the amount of ultrafine mineral admixture in the non-autoclaved pipe pile concrete is 50% to 60% of the total mass of cementitious materials.

[0017] Thirdly, the present invention provides a non-autoclaved pipe pile concrete, the raw materials of which are composed of cementitious materials, fine aggregates, coarse aggregates, water and water-reducing agents. The cementitious materials include cement and the above-mentioned ultrafine mineral admixtures, and the ultrafine mineral admixtures account for 50% to 60% of the total mass of the cementitious materials.

[0018] Preferably, the amount of cementitious material used is 410-460 kg / m³. 3 The water-cement ratio (mass of water in concrete / total mass of cementitious materials) is 0.29–0.34; the fine aggregate is river sand, with a dosage of 650–750 kg / m³. 3 The coarse aggregate is crushed stone, with two gradations: 5-12mm and 12-32.5mm (mass ratio 2:8), and a total usage of 1100-1200 kg / m³. 3 The water-reducing agent is a polycarboxylate-based high-efficiency water-reducing agent, and the dosage is 1.0% to 1.2% of the total mass of the cementitious material.

[0019] Preferably, the preparation method of the non-autoclaved pipe pile concrete is as follows: the concrete raw materials are mixed uniformly by mechanical stirring for 3 minutes to obtain the finished product. After the concrete is mixed and molded, it is cured with atmospheric pressure steam. The curing regime is as follows: heating to 80°C for 3 hours, holding at the temperature for 6 hours, and cooling down for 2 hours.

[0020] The present invention has the following beneficial effects:

[0021] (1) The ultrafine mineral admixture provided by the present invention uses ultrafine mineral powder as the main component and adds an appropriate amount of gypsum activator. The SO4 in the gypsum 2- It can react with active Al2O3 and SiO2 in ultrafine mineral powder to generate ettringite (AFt) and hydrated calcium silicate (CSH) gel, and has a significant sulfate activation effect on the early hydration of ultrafine mineral powder. When used in non-autoclaved pipe pile concrete, it can effectively improve the early strength.

[0022] (2) Compared with conventional S95 mineral powder, the admixture of the present invention can reduce the amount of cement used when replacing 50% to 60% of cement, while improving the early strength of concrete. After normal pressure steam curing, the 1-day compressive strength of concrete with the admixture of the present invention can be increased by 15% to 30% compared with concrete with the same amount of S95 mineral powder.

[0023] (3) The admixture formula of the present invention only requires two components, ultrafine mineral powder and gypsum activator, to achieve excellent activation effect. No other chemical activator components need to be added, resulting in low production cost and convenient batching.

[0024] (4) This invention can consume a large amount of industrial by-product gypsum, realize the high-value utilization of industrial solid waste resources, and has significant environmental benefits. Detailed Implementation

[0025] To better understand the above-mentioned technical solutions of the present invention, the technical solutions of the present invention will be further described below in conjunction with embodiments.

[0026] In addition to ultrafine mineral powder and gypsum activator, the main raw materials used in the embodiments also include:

[0027] S95 grade mineral powder: specific surface area 430m² 2 / kg, 78% activity index at 7d, and 97% activity index at 28d;

[0028] Cement: P·II52.5 Portland cement;

[0029] Aggregate: River sand (fineness modulus 2.8), 5~32.5mm crushed stone, using two gradations of 5~12mm and 12~32.5mm, with a mass ratio of 2:8;

[0030] Water-reducing agent: Slump-retaining polycarboxylate superplasticizer (SKY 8860), water reduction rate 30%.

[0031] Example 1 (460kg / m 3 Adhesive material (60% mineral admixture)

[0032] In this embodiment, the ultrafine mineral powder is obtained by ultrafine grinding of granulated blast furnace slag, with a specific surface area of ​​609 m². 2 / kg, density 2.94g / cm³ 3 The fluidity ratio is 101%, the 7-day activity index is 109%, the 28-day activity index is 116%, the chloride ion content is 0.04%, the loss on ignition is 0.07%, and the sulfur trioxide content is 0.35%.

[0033] Gypsum activator: Uses industrial by-product fluorogypsum, with anhydrous calcium sulfate content of 92%, fluoride content of 0.8%, and a specific surface area of ​​440 m². 2 / kg.

[0034] The ratio of ultrafine mineral powder to gypsum activator is 90:10 by mass, and the two constitute a mineral admixture.

[0035] The admixture was used in the non-autoclaved pipe pile concrete, with a mix proportion of 460 kg / m³ of total cementitious material. 3 (of which cement 184kg / m)3 276 kg / m³ of admixture 3 ), River sand 699kg / m 3 1155 kg / m³ of crushed stone 3 Water 136kg / m 3 The water-reducing agent dosage is 1.0%. After the concrete is mixed and molded, it is cured with normal pressure steam. The curing regime is as follows: heat up to 80℃ for 3 hours, keep at a constant temperature for 6 hours, and cool down for 2 hours.

[0036] The concrete slump was 110 mm, the compressive strength after 1 day of steam curing was 76.7 MPa, the compressive strength after 3 days was 84.3 MPa, and the compressive strength after 28 days was 98.9 MPa.

[0037] Example 2 (440kg / m 3 Adhesive material (50% mineral admixture)

[0038] In this embodiment, the ultrafine mineral powder is obtained by ultrafine grinding of granulated blast furnace slag, with a specific surface area of ​​620 m². 2 / kg, density 2.98g / cm³ 3 The fluidity ratio is 104%, the 7-day activity index is 104%, the 28-day activity index is 118%, the chloride ion content is 0.04%, the loss on ignition is 0.07%, and the sulfur trioxide content is 0.33%.

[0039] Gypsum activator: Industrial by-product fluorogypsum, anhydrous calcium sulfate content 94%, fluoride content 0.6%, specific surface area 462 m² 2 / kg.

[0040] The ratio of ultrafine mineral powder to gypsum activator is 92:8 by mass, and the two constitute a mineral admixture.

[0041] The admixture was used in the non-autoclaved pipe pile concrete, with a mix proportion of 440 kg / m³ of total cementitious material. 3 (of which cement 220kg / m) 3 220 kg / m³ of admixture 3 ), River sand 699kg / m 3 1155 kg / m³ of crushed stone 3 Water 136kg / m 3 The water-reducing agent dosage was 1.0%. The concrete preparation method and curing system were the same as in Example 1.

[0042] The concrete slump was 120 mm, the compressive strength after 1 day of steam curing was 73.2 MPa, the compressive strength after 3 days was 80.8 MPa, and the compressive strength after 28 days was 95.4 MPa.

[0043] Example 3 (410kg / m 3 Adhesive material (50% mineral admixture)

[0044] In this embodiment, the ultrafine mineral powder is obtained by ultrafine grinding of granulated blast furnace slag, with a specific surface area of ​​603 m². 2 / kg, density 2.99g / cm³ 3 The fluidity ratio is 105%, the 7-day activity index is 108%, the 28-day activity index is 117%, the chloride ion content is 0.05%, the loss on ignition is 0.06%, and the sulfur trioxide content is 0.32%.

[0045] Gypsum activator: Industrial by-product fluorogypsum, anhydrous calcium sulfate content 95%, fluoride content 0.6%, specific surface area 455 m² / g. 2 / kg.

[0046] The ultrafine mineral powder and gypsum activator are mixed in a mass ratio of 95:5, and the two constitute a mineral admixture.

[0047] The admixture was used in the non-autoclaved pipe pile concrete, with a mix proportion of 410 kg / m³ of total cementitious material. 3 (of which cement 205kg / m) 3 205 kg / m³ of admixture 3 ), River sand 699kg / m 3 1155 kg / m³ of crushed stone 3 Water 136kg / m 3 The water-reducing agent dosage was 1.0%. The concrete preparation method and curing system were the same as in Example 1.

[0048] The concrete slump was 120mm, the compressive strength after 1 day of steam curing was 69.5MPa, the compressive strength after 3 days was 76.2MPa, and the compressive strength after 28 days was 89.6MPa.

[0049] Comparative Example 1 (Baseline Group, 460 kg / m²) 3 Adhesive material, 60% S95 mineral powder and gypsum)

[0050] This comparative example uses S95 mineral powder and fluorogypsum as admixtures.

[0051] The concrete mix proportion is: total cementitious material 460 kg / m³ 3 (of which cement 184kg / m) 3 S95 mineral powder 239kg / m 3 Fluorogypsum 37kg / m 3 ), River sand 699kg / m 3 1155 kg / m³ of crushed stone 3 Water 136kg / m 3 The water-reducing agent dosage was 1.0%. The concrete preparation method and curing system were the same as in Example 1.

[0052] The concrete slump was 115 mm, the compressive strength after 1 day of steam curing was 62.5 MPa, the compressive strength after 3 days was 80.2 MPa, and the compressive strength after 28 days was 85.8 MPa.

[0053] Comparative Example 2 (Base Group, 440 kg / m²) 3 Adhesive material, 50% S95 mineral powder and gypsum)

[0054] This comparative example uses S95 mineral powder and fluorogypsum as admixtures.

[0055] The concrete mix proportion is: total cementitious material 440 kg / m³ 3 (of which cement 220kg / m) 3 S95 mineral powder 176kg / m 3 Fluorogypsum 44kg / m 3 ), River sand 699kg / m 3 1155 kg / m³ of crushed stone 3 Water 136kg / m 3 The water-reducing agent dosage was 1.0%. The concrete preparation method and curing system were the same as in Example 1.

[0056] The concrete slump was 125 mm, the compressive strength after 1 day of steam curing was 63.6 MPa, the compressive strength after 3 days was 67.2 MPa, and the compressive strength after 28 days was 80.2 MPa.

[0057] Comparative Example 3 (Baseline Group, 410 kg / m²) 3 Adhesive material, 50% S95 mineral powder and gypsum)

[0058] This comparative example uses S95 mineral powder and fluorogypsum as admixtures.

[0059] The concrete mix proportion is: total cementitious material 410 kg / m³ 3 (of which cement 205kg / m) 3 S95 mineral powder 164kg / m 3 Fluorogypsum 41kg / m 3 ), River sand 699kg / m 3 1155 kg / m³ of crushed stone 3 Water 136kg / m 3 The water-reducing agent dosage was 1.0%. The concrete preparation method and curing system were the same as in Example 1.

[0060] The concrete slump was 130 mm, the compressive strength after 1 day of steam curing was 58.9 MPa, the compressive strength after 3 days was 61.5 MPa, and the compressive strength after 28 days was 74.9 MPa.

[0061] Table 1. Comparison of mixing ratios and performance between each embodiment and the comparative example.

[0062]

[0063] Table 1 shows that, under the same cementitious material dosage and admixture ratio, the compressive strength at each age of the three sets of examples is significantly higher than that of the comparative example with S95 mineral powder admixture. Specifically, 460 kg / m³... 3 Under the condition of adhesive material, the 1-day compressive strength of Example 1 increased from 62.5 MPa to 76.7 MPa compared to Comparative Example 1, an increase of 22.7%, and the 28-day strength increased by 15.3%; under the condition of 440 kg / m³ adhesive material, the 1-day compressive strength of Example 2 increased by 15.1% compared to Comparative Example 2, and the 28-day strength increased by 18.9%; under the condition of 410 kg / m³ adhesive material, the 1-day compressive strength of Example 2 increased by 15.1%, and the 28-day strength increased by 18.9%; 3 Under the condition of adhesive material, the 1-day compressive strength of Example 3 was increased by 18.0% and the 28-day strength was increased by 19.6% compared with Comparative Example 3. In Examples 1-3, the strength decreased gradually with decreasing adhesive material content but remained at a relatively high level of 410 kg / m². 3 The 1-day strength of the adhesive material remained close to 70 MPa, indicating that the admixture of this invention has excellent reinforcing effects across a wide range of adhesive material dosages. Regarding workability, the slump of the example was basically the same as the comparative example, meeting the workability requirements for pipe pile forming. The above results demonstrate that the ultrafine mineral powder admixture of this invention has a significant strength advantage over conventional S95 mineral powder, and the combination of the two can achieve a synergistic improvement in the early and later strength of concrete under autoclaving-free conditions.

[0064] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.

Claims

1. An ultrafine mineral admixture for autoclaved aerated concrete pipe piles, characterized in that, It is composed of ultrafine mineral powder and gypsum activator.

2. The ultrafine mineral admixture for non-autoclaved concrete pipe piles according to claim 1, characterized in that, The ultrafine mineral powder is ultrafine slag powder obtained by ultrafine grinding of granulated blast furnace slag, and the gypsum activator is at least one of desulfurized gypsum, phosphogypsum or fluorogypsum.

3. The ultrafine mineral admixture for non-autoclaved concrete pipe piles according to claim 2, characterized in that, The ultrafine mineral powder has a specific surface area ≥600m² / kg, a density of 2.8~3.0g / cm³, a fluidity ratio ≥100%, a 7d activity index ≥104%, a 28d activity index ≥115%, a chloride ion content ≤0.06%, a loss on ignition ≤1.0%, and a sulfur trioxide content ≤0.5%.

4. The ultrafine mineral admixture for non-autoclaved concrete pipe piles according to claim 2, characterized in that, The gypsum activator contains ≥80% calcium sulfate dihydrate or anhydrous calcium sulfate and has a specific surface area of ​​300–600 m² / kg.

5. The ultrafine mineral admixture for non-autoclaved concrete pipe piles according to claim 1, characterized in that, The ultrafine mineral powder and gypsum activator are mixed in a mass ratio of (80-95):(5-20).

6. The application of the ultrafine mineral admixture according to any one of claims 1 to 5 in the preparation of autoclaved aerated concrete (AAC) for pipe piles, characterized in that, The application method involves incorporating ultrafine mineral admixtures into the non-autoclaved pipe pile concrete in a manner that partially replaces cement.

7. The application according to claim 6, characterized in that, The amount of the ultrafine mineral admixture in the non-autoclaved pipe pile concrete is 50% to 60% of the total mass of cementitious materials.

8. A type of non-autoclaved concrete pipe pile, characterized in that, The concrete is composed of cementitious materials, fine aggregates, coarse aggregates, water and water-reducing agents. The cementitious materials include cement and ultrafine mineral admixtures as described in any one of claims 1 to 5, wherein the ultrafine mineral admixtures account for 50% to 60% of the total mass of the cementitious materials.

9. The non-autoclaved concrete pipe pile according to claim 8, characterized in that, The amount of the cementitious material used is 410-460 kg / m³. 3 The water-cement ratio is 0.29–0.34; the fine aggregate is river sand, with a dosage of 650–750 kg / m³. 3 The coarse aggregate is crushed stone, with two gradations: 5-12mm and 12-32.5mm, at a mass ratio of 2:8, and a total usage of 1100-1200 kg / m³. 3 The water-reducing agent is a polycarboxylate-based high-efficiency water-reducing agent, and the dosage is 1.0% to 1.2% of the total mass of the cementitious material.